Aspek Klinis dan Diagnosis Kandidiasis Vulvovaginal - Nora Harminarti (Fakultas Kedokteran Universitas Riau, 2020)
Candidiasis vulvovaginal is an infection of the vaginal and vulva area caused by yeast Candida. The most causative species is Candida albicans. This fungus is commensal in the vagina but it can become a pathogen, causing the infection under certain conditions. Several conditions can be risk factors for this infection. Women are mostly getting infections, especially of productive age. Complaints experienced cause disturbances in the form of itching accompanied by abnormal vaginal discharge. The clinician can make diagnostics based on anamnesis, clinical and microscopic examination. This paper provides information about the causes, risk factors, clinical symptoms, and laboratory testing.